EVALUATION OF THE LUSTRATION POLICY IN LITHUANIA - Ravaitytė, Julija (Politologija, 2015)
In comparative studies of transitional justice in post-communist Central and Eastern Europe, Lithuania is ranked among the countries which have taken the strictest lustration measures. In contrast, a very negative perception of the issue dominates the Lithuanian public discourse. Lustration is often described as impotent or failed in the media. Despite its high political importance, there has been no systemic analysis evaluating the results of Lithuania’s lustration policy (LLP). This article aims at analyzing the effectiveness of LLP. The effectiveness is defined through achieving the official goals set by the policy-makers, which leads to the main research question: has the lustration policy in Lithuania achieved its goals?The main object of this article is the LLP which consists of three sets of laws: 1998 laws aimed at restricting the former KGB employees, 1999 law aimed at KGB’s secret collaborators, and 2010 law allowing publishing remaining KGB documents.Analysis is primarily based on semi-structured interviews with the key officials, who formed and implemented Lithuania’s lustration policy. Besides, the content analysis of press coverage, legislative acts, and transcripts of Parliamentary sessions were employed.LLP was expected to achieve three main objectives: (1) to ensure state security by banning supposedly disloyal persons from strategically important institutions; (2) to ensure state security by protecting former secret collaborators from blackmailing and manipulation by foreign secret services; (3) to inform the society about the system and practices of the former KGB. While analyzing these goals, two aspects were taken into consideration: (a) whether the legislation has created favorable conditions for their implementation; (b) whether the expected results were achieved by implementing the lustration measures.The first goal was achieved only partly. Although the former KGB employees were successfully banned from selected positions for the following ten years, the secret collaborators were mostly unaffected by the law. Moreover, one group formerly associated with KGB – the reserve officers – was not included in the legislation and therefore was not affected by the LLP.Ensuring protection from blackmailing was aimed at the former secret collaborators only, because many of their files were missing and accessible to either the government of the Russian Federation or private persons. This goal has been achieved rather effectively. More than 1500 people confessed having collaborated with the KGB. Their identities were classified ensuring their protection in case of blackmailing. As a result, the use of the entire former KGB network was impeded, because the identities of those, who confessed, were concealed and the risks associated with contacting former collaborators were significantly enhanced.The last goal – to inform society – was achieved as well, although its implementation was overdue and slow. The first efforts to achieve publicity failed due to the ineffective work of the Lustration Commission and the insufficient KGB archive. However, legislation adapted in 2010 enabled the Genocide and Resistance Research Centre of Lithuania to publish all accessible KGB documents. This initiative helped the society learn about the former KGB; however, its implementation started only in 2011 and is still ongoing.This article corresponds with the last wave of transitional justice studies, in which the results and/or impact of transitional justice measures is evaluated. Besides offering an evaluation of Lithuania’s lustration policy, the analysis provides ground for further research. Firstly, it allows comparing Lithuania with other post-communist countries, which have chosen similar transitional justice measures. Secondly, the material analyzed in this paper can be used for a wider theoretical assessment of lustration’s goals, factors, determining its effectiveness, etc. Finally, this study can serve for the further research of Lithuania’s lustration policy. The findings of this article suggest a rather positive evaluation of LLP, further contradicting the opinion dominant in the local media. This could encourage future studies to explore the reasons of this inconsistency.